Mapping Rora expression in resting and activated CD4+ T cells - Haim-Vilmovsky, Liora; Henriksson, Johan; Walker, Jennifer A.; Miao, Zhichao; Natan, Eviatar; Kar, Gozde; Clare, Simon; Barlow, Jillian L.; Charidemou, Evelina; Mamanova, Lira; Chen, Xi; Proserpio, Valentina; et al. (PLOS ONE, 2021)
The transcription factor Rora has been shown to be important for the development of ILC2 and the regulation of ILC3, macrophages and Treg cells. Here we investigate the role of Rora across CD4+ T cells in general, but with an emphasis on Th2 cells, both in vitro as well as in the context of several in vivo type 2 infection models. We dissect the function of Rora using overexpression and a CD4-conditional Rora-knockout mouse, as well as a RORA-reporter mouse. We establish the importance of Rora in CD4+ T cells for controlling lung inflammation induced by Nippostrongylus brasiliensis infection, and have measured the effect on downstream genes using RNA-seq. Using a systematic stimulation screen of CD4+ T cells, coupled with RNA-seq, we identify upstream regulators of Rora, most importantly IL-33 and CCL7. Our data suggest that Rora is a negative regulator of the immune system, possibly through several downstream pathways, and is under control of the local microenvironment.